(untitled) (Scientific journal of the Fergana State University, 2025)
This article evaluates the effectiveness of a set of exercises aimed at improving the physical conditioning of 11-year-old freestyle wrestlers. The research results indicate that regular exercise significantly increases the athletes’ strength, endurance, and agility. These exercises play a crucial role in enhancing the overall physical condition of the athletes and preparing them for competitions.